Telehealth perceptions and associated factors among older adults with chronic conditions in Saudi Arabia: a comparative study of users and non-users - Meraya, Abdulkarim M.; Khardali, Amani; Ahmad, Sarfaraz; Hoshaibari, Ahmed Z.; Alameer, Atheer A.; Jaafari, Raed Y.; Thaibah, Hilal A.; Alfarhan, Moaddey; Syed, Mamoon H. (Frontiers in Public Health, 2025)
BackgroundTelehealth is a promising approach for healthcare delivery that uses telecommunication technologies to enhance accessibility by providing remote health services. This study aimed to identify psychosocial factors that best predict behavioral intention to use telehealth/telemedicine, as mediated by attitude toward use, among older adults with chronic conditions in the Jazan region of Saudi Arabia, and to compare users and non-users.MethodsParticipants were aged 60 years or above, residing in Jazan, and presenting with at least one chronic condition. This study used a quantitative research approach with a cross-sectional questionnaire survey. We stratified all analyses by telehealth use status (users or non-users).ResultsOur study sample comprised 466 participants aged 60 or above with at least one chronic condition. The most prevalent condition was diabetes (29%), followed by arthritis (23%). Among the telehealth users (n = 256), a high percentage (42%) reported that telehealth was better than in-person appointments. Among telehealth users, we found that perceived usefulness [(users: β = 0.501; p < 0.001) (non-users: β = 0.441; p < 0.001)] and facilitating conditions [(users: β = 0.768; p = 0.001) (non-users: β = 0.807; p < 0.001)] positively affected attitudes to using telehealth. Telehealth users and non-users reported dislike or fear of the service and unavailability of appointments as the most important barriers to using telehealth services.ConclusionThe results of this study are important for designing new telehealth applications, especially for older adults in Saudi Arabia. Designers and developers must understand that the attributes and capabilities of telehealth applications should be simple and user-friendly to encourage older adults to increase their intention to use telehealth.